Motivasi Tenaga Kerja RSD Mangusada Badung-Bali dalam Mempelajari Bahasa Inggris - Ketut Santi Indriani (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This study aims to identify the categories of motivation and appropriate stimulants for the RSD Mangusada staffs in learning English. This research is a qualitative research with method of collecting data using questionnaire distributed to 50 staff of RSD Mangusada from various divisions. The questionnaire contains closed questions that are filled out using Likert’s scale. The data in this study were analyzed descriptive-qualitatively by describing the categories of motivation in learning English. The results of the data analysis show that there are five categories of single dominant motivation and three categories of combined dominant motivation possessed by the staff of Mangusada Badung Hospital in learning English, those are intrinsic dominant motivation category, extrinsic dominant, integrative dominant, instrumental dominant, amotivation dominant, intrinsic- integrative dominant, intrinsic-instrumental dominant and extrinsic-instrumental dominant. Based on the results of the data analysis, it can be concluded that the main factor which encourages Mangusada Hospital staffs to learn English is only limited to the desire to fulfill practical needs, such as the desire to get a better job and/or to get a higher income. The desire to fulfill this practical need arises both from within the learners and from the environment. Thus, if RSD Mangusada needs to improve the English competence of all its staff in order to improve services, pragmatic stimulants is needed in order to get an optimal result.